KINEMATIC METHOD OF CALCULATING THE VALUES OF MOMENTS IN THE MOST DANGEROUS SECTIONS OF BEAMS (Збірник наукових праць Галузеве машинобудування будівництво, 2017)
The method of applying technique of the kinematic limit equilibrium method was given.Formulas for calculating the values of the bending moments for reinforced concretestructures and their advantages over conventional static method, which is based on theequations of equilibrium was also derived. In this article there is shown how this method isused for the most widely-spread reinforced concrete elements in the building industry whichhave a great deal with bending. The simply supported beams are mostly used as suchelements. They are with position fixed ends in this article. There are three kinds of loads forabove mentioned beams: by one concentrated force within limits of the beam, by the uniformload over the full span and by two concentrated forces which are pointed symmetrically aboutthe central axe of the beam and spaced at certain intervals apart.Keywords: the kinematic method, the limit equilibrium method, the virtual work, theplastic hinge, the bending moment.